Formulation and optimization of fast dissolving intraoral drug delivery system for clobazam using response surface methodology - Rajni Bala; Sushil Khanna; Pravin K Pawar (Wolters Kluwer Medknow Publications, 2013)
Clobazam is a newer 1,5-benzodiazepine used for the treatment of epilepsy. It is better tolerated and less sedating than other benzodiazepines. Absorption of the drug can be impacted by oral fast dissolving dosage form; this may have implications for epilepsy in pediatrics and those having difficulty in swallowing tablets/capsules resulting in improved patient compliance. The purpose of the present investigation was to formulate and optimize clobazam oro-dissolving tablets by direct compression method using response surface methodology (RSM). Oro-dispersible tablets of clobazam were prepared by direct compression method using crospovidone (2-6%) as a superdisintegrant, microcrystalline cellulose (MCC) (20-40%) was used as diluents along with directly compressible mannitol to enhance mouth feel. A 3 2 full factorial design was applied to investigate the combined effect of two formulation variables: amount of crospovidone and MCC over the independent variables disintegration time, wetting time and percent drug release. Disintegration time showed by all formulations was found to be in the range of 24.3-193 s based on evaluation parameters the formulation containing 6% of crospovidone and 30% of MCC showed promising performance against all other formulations. The results demonstrated that the RSM could efficiently be applied for the formulation of clobazam oro-dispersible tablets; therefore, constitute an advance in the management of epileptic attacks.